THE INFLUENCE OF SCHOOL ENVIRONMENT ON THE STUDY DISCIPLINE OF ACCOUNTING STUDENTS AT SMK NEGERI 6 MAKASSAR - nugiyanti, Tari; Hasyim, Sitti Hajerah; Azis, Fajriani (Universitas Labuhanbatu, 2023)
The research carried out had the aim of analyzing the influence of the school environment on the learning discipline of accounting students at SMK Negeri 6 Makassar. The research carried out also used a variable in the form of school environment as the independent variable and learning discipline as the dependent variable. As with carrying out the research using the population with all accounting students at SMK Negeri 6 Makassar. In determining the research sample according to the criteria determined in the research, a Proportionate Stratified Random Sampling technique was used, in this case the sample size was 71 students. The research also used a technique to collect research data in the form of documentation and questionnaires. The data collected from this research was discussed using descriptive analysis data analysis techniques, instrument testing, classical assumption testing, and hypothesis testing. In a simple linear regression analysis that has been produced in the school environment, Y=6.383 + 0.387 On the other hand, in the product moment correlation test, a correlation coefficient assessment of 0.798 was obtained and it was declared to be in the high category, meaning that the school environment has a high influence on learning discipline. In an analysis of the coefficient of determination (r2), an assessment was obtained (r2) = 0.637 or 63.7%, which means that the school environment has a contribution to learning discipline of 63.7 percent and the remaining 36.3 percent is found to be influenced by other factors. Another case, in the t-test analysis, results were obtained with a significant assessment of 0.000 < 0.05, which can be interpreted as the school environment having a significant influence on the level of learning discipline, as well as on the acceptance of the hypothesis.Keywords: School Environment, Learning Discipline. AbstrakPada penelitian yang dilakukan mempunyai sebuah tujuan guna menganalisis pengaruh lingkungan sekolah pada kedisiplinan belajar siswa akuntansi di SMK Negeri 6 Makassar. Penelitian yang dilakukan pula menggunakan sebuah variabel berupa lingkungan sekolah menjadi variabel bebas dan kedisiplinan belajar sebagai variabel terikat. Sebagaimana pelaksanakan penelitian menerapkan populasi dengan keseluruhan siswa akuntansi di SMK Negeri 6 Makassar. Dalam menentukan sampel penelitian yang sesuai kriteria yang telah ditentukan dalam penelitian digunakan sebuah Teknik Proportionate Stratified Random Sampling, dalam hal ini didapatkan pada suatu populasi yang ditentukan didapatkan banyaknya sampel 71 siswa. Penelitian yang dilakukan juga menggunakan sebuah teknik untuk mengumpulkan data penelitian yang berupa dokumentasi dan angket. Dalam data yang terkumpul dari penelitian ini dilakukan pembahasan menggunakan Teknik Analisis data analisis deskriptif, uji instrument, uji asumsi klasik, dan uji hipotesis. Dalam sebuah analisis regresi linear sederhana yang telah dihasilkan dalam lingkungan sekolah Y=6,383 + 0,387X sebagaimana dapat diartikan setiap dilakukan penambahan 1 nilai lingkungan sekolah, menjadikan penilaian sebuah kedisiplinan belajar terjadi peningkatan yang besarnya 0,387. Lain halnya dalam pengujian korelasi product moment didapatkan sebuah penilaian kofisisen koralsi 0,798 dan dinyatakan berkategori tinggi sebagaimana diartikan lingkungan sekolah berpengaruh tinggi terhadap kedisipiplinan belajar. Dalam sebuah analisa koefisien determinasi (r2) didapatkan sebuah penilaian (r2) = 0,637 atau 63,7% dengan diartikan lingkungan sekolah memiliki kontribusi pada kedisiplinan belajar yang besarnya 63,7 persen dan diperoleh sisa 36,3 persen didapatkan sebuah pengaruh dari faktor lainnya. Lain halnya dalam analisa uji-t diperoleh yang dihasilkan dengan penilaian signifikan 0.000 0,05 sebagaimana dapat diartikan dengan lingkungan sekolah memberi pengaruh secara signifikan pada tingkat kedisiplinan belajar, serta juga untuk hipotesis diterimanya.Kata Kunci: lingkungan Sekolah, Kedisiplinan Belajar